Akodon polopi Jayat et al., 2010 is a senior subjective synomym of Akodon viridescens Braun et al., 2010 - D Elía, Guillermo (2011)
Two new taxa of species level were recently named for grass mice of the genus Akodon (Cricetidae, Sigmodontinae) from central Argentina: Akodon polopi Jayat, Ortiz, Salazar-Bravo, Pardiñas et D’Elía, 2010 and Akodon viridescens Braun, Mares, Coyner et Van Den Bussche, 2010. Several lines of evidence show that both taxa refer to the same biological species. Various morphologic characters enumerated by the two research teams for A. polopi and A. viridescens are coincident. The brownish coloration of the dorsal pelage, the chin with a small but distinguishable white patch, the tail of approximately 70% of head and body length, and the broad rostrum are among the diagnostic characters cited for both forms. Other additional characters mentioned in the diagnosis of only one of the nominal forms are also enumerated in the general description of the other. These include the size intermediate for the genus, the hour-glass shaped interorbital region with sharply squared posterior margins in older individuals, the anterior border of mesopterygoid fossa rounded with sides parallel or slightly diverging backward, and the parapterygoid fossae with straight and gradually divergent sides. Many additional features are mentioned for both nominal forms in their general descriptions.